1993
DOI: 10.1172/jci116216
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of human erythroid colony-forming units by tumor necrosis factor requires beta interferon.

Abstract: We have previously reported that inhibition ofhuman CFU-erythroid (E) colony formation by tumor necrosis factor (TNF) is an indirect effect mediated by a soluble factor released from a fraction of marrow accessory cells which are predominantly stromal elements (Means, R. T., Jr., E. N. Dessypris, and S. B. Krantz. 1990. J. Clin. Invest. 86:538-541). Further studies reported here identify a mediator of this effect.The inhibitory effect of recombinant TNF on marrow CFU-E is ablated by neutralizing antibodies to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
1
7

Year Published

1995
1995
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(78 citation statements)
references
References 17 publications
1
69
1
7
Order By: Relevance
“…Subsequent in vitro studies, however, showed that the inhibitory effect of TNF-a on erythropoiesis at the CFU-E level was likely mediated by IFN-b released by macrophages in response to TNF-a and not due to a direct effect of TNF-a on erythroid progenitors. 67,68 However, in another study, a direct effect of TNF-a on erythroid progenitors (BFU-E) was suggested, mediated by the TNF-R1. 69 A direct effect of TNF-a on erythroid cells was supported by subsequent studies.…”
Section: Role Of Cell Death Receptors In the Control Of Erythropoiesismentioning
confidence: 96%
“…Subsequent in vitro studies, however, showed that the inhibitory effect of TNF-a on erythropoiesis at the CFU-E level was likely mediated by IFN-b released by macrophages in response to TNF-a and not due to a direct effect of TNF-a on erythroid progenitors. 67,68 However, in another study, a direct effect of TNF-a on erythroid progenitors (BFU-E) was suggested, mediated by the TNF-R1. 69 A direct effect of TNF-a on erythroid cells was supported by subsequent studies.…”
Section: Role Of Cell Death Receptors In the Control Of Erythropoiesismentioning
confidence: 96%
“…28 TNF-␣ has been shown to inhibit erythropoiesis, [29][30][31] although it has been demonstrated that the inhibitory effects of TNF-␣ were likely mediated by ␤-interferon produced by macrophages in response to TNF-␣ and not due to direct actions of TNF-␣. 32,33 TNF-␣ also has been reported to promote proliferation of CD34 ϩ human hematopoietic cells. 34 The direct action of TNF-␣ on erythroid cells therefore remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Erythropoetin levels below those expected for the degree of anemia have been demonstrated in septic and critically ill patients [69,70]. There is evidence that inflammatory cytokines have play an inhibitory role on erythropoietin production as well as a direct inhibitory effect on erythroid progenitor cell production in the bone marrow [71][72][73][74][75].…”
Section: Erythropoesismentioning
confidence: 99%